A Study of Financial Management Planning (Budget) for 2012 at State Government of Kedah, Malaysia - Ramadhan, Surya (2013)
This paper describes the budgeting process of in 2012 at State Treasury, State Kedah Government. Based on the financial procedures of Federal Government, and State Kedah regulations and policy, all departments and agencies need to follow the financial procedures, as part of the budgeting process. The collection of data were done by interviews and document analysis at Kedah State Treasury. The interviews were done by asking several officers in Budget Unit and Finance Unit. The document analysis was done by reading the regulation and policy book, and Circulars (including of Federal and State), Treasury Instruction No. 29 and 31, Finance Circular Letter–Annual Expenditure Provision Procedure, Budget Book 2012, Additional Budget File 2012. The implementation of budget 2012 was only for 10 months periods (March 2011 to January 2012). The budgeting process at State Kedah is divided into 4 (four) components : Preparation, Approves, Execution, and Auditing. Preparation covers providing Circulars by State Treasury, acceptance and checking budget draft from departments, presentation in front of EXCO and DUN for approval. Approves, started with checking the completeness of the budget draft for departments, presentation in front of EXCO and DUN for obtaining approval. Execution, encompasses provision warrant and sub warrant to departments. Budget in 2012 emphasis on four strategies: (1) Enhancing Economic Growth, which consist of three sub-strategy, Strengthening Agricultural In Business, Increase Tourism Industry Potential, Promoting The Manufacturing Industry, (2) Improving People Livelihood, encompass Affordable Houses and Quality of Life, (3) Improving Human Capital, and (4) Strengthening State Corporate Governance. The budgetary process at State Kedah Government, follows Malaysian Budgeting System, also known as Modified Budgeting System (MBS). MBS contain 4 (four) components, (i) Expenditure Target; (ii) Program Agreements and Exceptions Reports; (iii) Cycle of Program Evaluations; and (iv) a more Generalized Approach to Expenditure Control. Some elements that are considered together in the financial management toward public welfare includes: Transparency: This refers to efforts by local governments to make information publicly available in a systematic way at each stage of the budget cycle. Participation: This refers to the involvement of civil society in decision making at every stage of the budget cycle. Accountability: This refers to the extent to which local governments render an account of their management of budgets to both local legislative assemblies (DPRA) and the public generally. Gender Equality: This refers to efforts by local governments to provide space for the poor and women to take part in the budget cycle.